Medial Plica Syndrome of the Knee: Arthroscopic Plica Resection versus Structured Physiotherapy—A Randomized Controlled Trial - Sauer, Steffen; Karlsen, Gitte; Miller, Lene; Storm, Jens Ole (The Surgery Journal, 2022)
Background Medial plica syndrome is a commonly overlooked cause of anterior knee pain. A consensus on diagnosis and treatment is yet to be found. This study compares the clinical outcome of arthroscopic plica resection with structured physiotherapy for patients with isolated medial plica syndrome in a prospective randomized controlled trial with a 2-year follow-up.Methods Forty-eight patients have been included in this prospective randomized controlled trial presenting medial plica syndrome. Patients were randomly assigned to either arthroscopic plica resection or structured physiotherapy. The primary outcome was the change in the average score of the Lysholm knee scoring scale from baseline to 2-year follow-up.Results Mean baseline Lysholm score for patients assigned to arthroscopic plica resection and physiotherapy was 65.8 and 66.3, respectively. No significant difference was seen between the two groups. Thirty-three patients were assessed at 2 years follow up. The mean Lysholm score was 89.7 for patients assigned to arthroscopic plica resection and 74.6 for patients assigned to structured physiotherapy. A statistically significant difference was seen between the two groups (p = 0.007).Conclusions Arthroscopic plica resection was associated with significantly greater clinical improvement compared with physiotherapy at 2-year follow-up.
Keywords: knee; medial plica; plica syndrome